ANALISIS PENGARUH SERTIFIKASI TANAH TERHADAP PENINGKATAN NILAI EKONOMI TANAH MELALUI KEPASTIAN STATUS HUKUM: KAJIAN LITERATUR - Khalimi Khalimi; Gunawan Widjaja; Cecep Suhardiman (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to analyse the effect of land certification on increasing land economic value through legal certainty, using a literature review method. Land certification, as a process of granting legal documents, provides legal certainty over land ownership, which in turn contributes to increasing land economic value. Through a literature review of various previous studies, it was found that legal certainty reduces the risk of disputes and increases market and financial institution confidence, so that certified land tends to have higher prices, better liquidity, and wider access to financing. These findings underscore the importance of land certification as a strategic instrument in strengthening land governance and promoting local and national economic growth. This study recommends accelerating and expanding land certification programmes as an effective policy measure in creating legal certainty and sustainable economic value of land.